Calcium-induced conformational changes of Thrombospondin-1 signature domain: implications for vascular disease. (4th May 2017) - Gupta, Akanksha; Agarwal, Rahul; Singh, Ashutosh; Bhatnagar, Sonika
Abstract: Context: Thrombospondin1 (TSP1) participates in numerous signaling pathways critical for vascular physiology and disease. The conserved signature domain of thrombospondin 1 (TSP1-Sig1) comprises three epidermal growth factor (EGF), 13 calcium-binding type 3 thrombospondin (T3) repeats, and one lectin-like module arranged in a stalk-wire-globe topology. TSP1 is known to be present in both calcium-replete (Holo-) and calcium-depleted (Apo-) state, each with distinct downstream signaling effects. Objective: To prepare a homology model of TSP1-Sig1 and investigate the effect of calcium on its dynamic structure and interactions. Methods: A homology model of Holo-TSP1-Sig1 was prepared with TSP2 as template in Swissmodel workspace. The Apo-form of the model was obtained by omitting the bound calcium ions from the homology model. Molecular dynamics (MD) simulation studies (100 ns) were performed on the Holo- and Apo- forms of TSP1 using Gromacs4.6.5. Results and discussion: After simulation, Holo-TSP1-Sig1 showed significant reorientation at the interface of the EGF1-2 and EGF2-3 modules. The T3 wire is predicted to show the maximum mobility and deviation from the initial model. In Apo-TSP1-Sig1 model, the T3 repeats unfolded and formed coils with predicted increase in flexibility. Apo-TSP1-Sig1model also predicted the exposure of the binding sites for neutrophil elastase, integrin and fibroblast growth factor 2. We present a structural model and hypothesis for the role of TSP1-Sig1 interactions in the development of vascular disorders. Conclusion: The simulated model of the fully calcium-loaded and calcium-depleted TSP1-Sig1 may enable the development of its interactions as a novel therapeutic target for the treatment of vascular diseases.